2021
DOI: 10.3389/fgene.2021.798161
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Stem Cells: Their Research Potential and Limitations

Abstract: In the era of growing interest in stem cells, the availability of donors for transplantation has become a problem. The isolation of embryonic and fetal cells raises ethical controversies, and the number of adult donors is deficient. Stem cells isolated from deceased donors, known as cadaveric stem cells (CaSCs), may alleviate this problem. So far, it was possible to isolate from deceased donors mesenchymal stem cells (MSCs), adipose delivered stem cells (ADSCs), neural stem cells (NSCs), retinal progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 126 publications
(199 reference statements)
0
10
0
Order By: Relevance
“…The main research on this topic has been extensively reviewed in Cieśla and Tomsia. 56 As seen from our experience on post-mortem vascular tissues, MSCs from cadaveric tissues retain stemness and differentiation features. Thus, the utilization of cadaveric sources for the isolation of MSCs provides for a promising investigation field to allow MSC-based therapies in terms of safety and effectiveness.…”
Section: Ethical Considerationsmentioning
confidence: 84%
“…The main research on this topic has been extensively reviewed in Cieśla and Tomsia. 56 As seen from our experience on post-mortem vascular tissues, MSCs from cadaveric tissues retain stemness and differentiation features. Thus, the utilization of cadaveric sources for the isolation of MSCs provides for a promising investigation field to allow MSC-based therapies in terms of safety and effectiveness.…”
Section: Ethical Considerationsmentioning
confidence: 84%
“…The high correlation coefficients between the blood and cartilage tissues for methanol suggest that methanol concentration in cartilage can be determined, and methanol behaves similarly to urine. Since the obtained results add another perspective to the distribution of xenobiotics in cartilage tissues, they may also be important in the context of using this type of tissue for regenerative medicine [ 34 ] or plastic surgery purposes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post mortem tissues represent plentiful alternative sources for such cellular therapies, in particular from young donors without signs of age-associated joint degeneration. Previous studies have shown that primary cells with MSC-like properties can be obtained from various tissues, even several days post mortem [ 15 , 16 , 18 , 22 , 23 , 24 ], and from tissues stored under cryoprotection for years [ 25 ]. However, comprehensive studies that include several tissues from human post mortem donors along with specific times post mortem are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues harvested from post mortem donors represent an alternative tissue source for isolating MSCs, particularly with the availability and ease of access to large numbers of biopsies [ 15 , 16 ]. Studies have shown that primary cells from various tissues of cadaveric donors can be isolated several hours, or even several days, post mortem [ 15 ].…”
Section: Introductionmentioning
confidence: 99%